Reply to Comment on "Photo‐Controlled Reversible Microtubule Assembly Mediated by Paclitaxel‐Modified Cyclodextrin". Issue 20 (20th March 2020) - Zhang, Ying‐Ming; Yu, Qilin; Liu, Yu
Abstract : In this Reply to a Correspondence, the importance of photo‐responsive noncovalent complexation in the modulation of microtubule morphology and aggregation behavior is emphasized. Meanwhile, the exclusive binding mode and mechanism need to be further investigated on account of multiple host–guest associations at the supramolecular level.